Autonomous Car Path Optimalization - Vladyka, V. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
This paper deals with path search and optimalisation of model car in unknown space. All data from sensors are processed in real-time onboard at ARM Cortex M4 microcontroller. Model’s main sensor is line-scan camera.
Keywords: image processing; robot; The Freescale Cup; selflocalization